1965
DOI: 10.1126/science.150.3693.226
|View full text |Cite
|
Sign up to set email alerts
|

Hemolysin of Mycoplasma pneumoniae : Tentative Identification as a Peroxide

Abstract: Mycoplasma pneumoniae produces a soluble hemolysin active against guinea pig erythrocytes. This hemolysin appears to be a peroxide, since catalase or peroxidase inhibits its activity. The action of catalase and peroxidase is specific, since heating the enzymes abolishes their effect on the hemolysin. In addition, 3-amino- 1,2,4-triazole, a potent inhibitor of catalase, reverses the inhibitory effect of the enzyme. The hemolysin of M. laidlawii is also a peroxide. The hemolysins of M. pneumoniae and M. laidlawi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

1966
1966
2010
2010

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 11 publications
4
50
0
Order By: Relevance
“…Based on previous reports (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(39)(40)(41)(42) and on the data presented in our study, the following pathogenetic events ofM. pneumoniae infection are suggested (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…Based on previous reports (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(39)(40)(41)(42) and on the data presented in our study, the following pathogenetic events ofM. pneumoniae infection are suggested (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…Virulence mechanisms in the pathogenicity of mycoplasma infection have been related to the generation of various products, including exotoxins (9), phospholipases (39,40,45), proteases (37), and urease (26), and to oxidative damage (43). Different groups have also reported that host DNA and RNA represent a potential target for membrane-associated and/or exported nucleases from mycoplasmas.…”
Section: Discussionmentioning
confidence: 99%
“…The hemolytic activity of M. pneumoniae is due to production of H 2 O 2 and is inhibited by catalase (264). In contrast, the hemolytic activity of ureaplasmas is not inhibited by catalase, suggesting an alternative enzyme system may be responsible (96).…”
Section: Secretory Productsmentioning
confidence: 99%